The effect of women managers in the board of directors of companies on the integrated reporting: example of Istanbul Stock Exchange (ISE) Sustainability Index - ARZOVA, SABRİ BURAK (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Sustainability reporting is the counterpart of the concept of non-financial reporting and an important element of integrated reporting that includes financial and non-financial information (GRI)(3). Integrated Reporting is described as a summary presentation of how an organization's strategy, management, performance, and expectations will create value (IIRC)(4). In integrated reporting, the information collected from different sources of institutions (finance, ecology, etc.) is established and evaluated, and uncertainties regarding the future activities of organizations are tried to be prevented and their sustainability is evaluated (Vaz et al. (2016)). This study works out the impact of gender diversity on companies' boards of directors on the quality of Integrated Reporting and firm performance. 15 companies that have ESG scores between 2014 and 2019 from 56 companies included in the ISE Sustainability Index (XUSRD) as of 03.02.2020 have been examined and reported using the Panel Data Analysis method. The ISE Sustainability Index allows investors to easily distinguish companies that develop sustainability and corporate social responsibility principles and invest in these companies. It also allows companies to compare their corporate sustainability performance locally and globally. For this reason, this index, which aims to increase understanding, knowledge, and practices on sustainability among ISE companies, is very important and it has been observed that the relationship between women on board of directors, firm performance, and ESG is not analyzed adequately.
Keywords: Environmental; social; and governance (ESG) disclosure; corporate social responsibility (CSR); women board directors; firm value; ISE Sustainability Index; CORPORATE GOVERNANCE; PERFORMANCE; ESG; DISCLOSURE; DIVERSITY